Karakteristik COVID-19 Pada Anak - Alfi Hakim (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction; COVID-19 is a new problem in the world of Health in all countries that have not been completely resolved until now. COVID-19 can infect anyone, including children. Objective; Assessing the incidence, transmission, symptoms, treatment, examination, classification, and management of COVID-19 in children. Method; Discuss the publication of 26 research articles on COVID-19 in children from various sources such as NCBI and Scholar from 2020-to 2022 and present them in relevant articles. Results; The incidence of COVID-19 in children is lower; clinical manifestations tend to be mild and asymptomatic than in adults. Transmission to children is mainly from the family. The classification of COVID-19 in children tends to be the same as in adults. Until now, no treatment for COVID-19 has been found, and only supportive therapy has been given. Conclusion; The incidence and clinical symptoms are milder than in adults, and children have a good prognosis.